Kompetensi SDM Bidang Kebandarudaraan - Siahaan, Juanda (Warta Penelitian Perhubungan, 2012)
Recently, there is increasing growth in passenger numbers every year that are passengers, aircraft, routes, airports will have implications for increasing the number of competent human resources based on competency standards in each of the functions and duties in airport services. This implementation was carried out at the Tjilik Riwut Palangkarya Airport. Primary data were collected by interview with airport managers and direct observation, whereas secondary data obtained from reports, articles and standards of airportscompetence. Problems for some personnel do not have a certificate/ license and most of the airtime is depleted and workload that owned for each airport personnel is high. Data were analyzed using qualitative descriptive analysis towards aviation human resources competency. Overview of the results obtained for the basis technician license are 56% of licensed skilled personnel and 44% do not yet have, personnel who have SKP 46% have a basic license Avsec, 7% Avsec junior license and basic absec 20%, 13% aviation security personnel who have Avsec junior license, 40% senior Avsec licensing and 47% basic Avsec license, 29% flight engineer education had educatilln D III PLLU, 35% DIV Allu, 12% D III PPA and the other below 10%, personnel licensing PKP-PK 43 % do not have a license, 34% have a basic license, 3% junior license and 20% of senior license.Keywords: Human Resources, Competency Standards.Pada tahun terakhir ini terns terjadi peningkatan pertumbuhan jumlah penumpang setiap tahun baik jumlah penumpang, pesawat, rute penerbangan, bandar udara akan berimplikasi pada penambahan jumlah sumber daya manusia yang berkompetensi sesuai standar kompetensi pada bidang masing-masing fungsi dan tugasnya dalam pelayanan jasa kebandarudaraan. Pelaksanaan ini dilaksanakan di bandar udara Tjilik Riwut Palangkarya. Data primer dikumpulkan, dengan teknik wawancara pengelola bandar udara serta observasi langsung, sedangkan data sekunder diperoleh dari laporan, artikel dan standar kompetensi bandar udara. Permasalahan sebagian personel belum memiliki sertifikat/lisensi dan sebagian besar masa berlakunya sudah habis serta beban kerja yang dimiliki setiap personel bandar udara cukup tinggi. Data dianalisis dengan menggunakan analisis deskriptif kualitatif terhadap kompetensi sumber daya manusia kebandarudaraan. Diperoleh gambaran hasil untuk lisensi teknisi landasan 56 % personel yang memiliki lisensi terampil dan 44 % belum memiliki, personel yang memiliki SKP 46% memiliki lisensi basic avsec, 7% lisensi junior avsec dan basic avsec 20%, personel keamanan penerbangan 13% yang memiliki lisensi junior avsec, 40% lisensi senior avsec dan 47% lisensi basic avsec, pendidikan teknisi penerbangan 29% memiliki pendidikan D III PLLU, 35% DIV ALLU, 12% D III PPA dan yang lainnya dibawah 10%, lisensi personel PKP-PK 43% belum memiliki lisensi, 34% memiliki lisensi basic, 3% lisensi junior dan 20% lisensi senior. Kata kunci : SDM bandara, Standar Kompetensi